Buying time: the effect of Market Facilitation Program payments on the supply of grain storage - Swearingen, Bryn (Kansas State University, 2021)
Over the past few years, the United States government has increased the amount of support given to producers through ad hoc payments. During the 2018-19 and 2019-20 marketing years, the US paid out a total of 23 million dollars of direct payments to farmers because of the trade tensions with China and other countries. This program was called the Market Facilitation Program (MFP). This study focuses on MFP and how the additional payments impacted on-farm stocks and farmer marketing decisions. We analyze this program using both theory and empirical estimates. Using Working’s Theory of Storage, we explain that the main mechanism that MFP payments impact the supply of storage is through a decrease to the opportunity cost to store grain. This decrease in opportunity cost of grain storage for farmers causes an increase in the supply of storage. To test this hypothesis empirically, we build a fixed effects model across multiple dimensions using state-level inventory data provided through the Grain Stocks report. The key to our identification strategy is that there is some portion of MFP payments that is uncorrelated with the trade-war price shock. Our analysis finds that MFP payments had a significant impact on grain storage by US farmers. In states with relatively higher payments at the marginal 10% increase in payments a 1.28% increase in on-farm inventories will occur holding all else constant. This study provides a baseline analysis of how these ad hoc policies can affect decision making. It is important to analyze these to be better informed of the unintentional effects these policies can have on farmers’ marketing and storage decisions.
Keywords: Ad hoc payments; Market Facilitation Program; Fixed effects; Grain storage